Analisis Kebijakan Mutasi Pegawai Negeri Sipil Pada Sekertariat Daerah Pemerintah Kota Ternate - Karianga, Hendra; Amalia, Rasty (Jurnal GeoCivic, 2023)
The background of this research is that the employee transfer policy is very important for civil servants within the Ternate City Government. The policy aims to 31 realize that regional head policies in carrying out mutations are realized as something that is absolutely necessary and these policies must be able to increase employee work productivity. If mutations are not carried out to increase the work productivity of employees, then something is not good in managing the area. The problem in this research is how the transfer policy is and what obstacles are faced by civil servants at the Regional Secretariat of the Ternate City Government in the Transfer of Employees. The purpose of this study was to determine the transfer policy, as well as to find out the obstacles in the transfer of employees at the Regional Secretariat of the Ternate City Government. Data collection techniques used are questionnaires, interviews, and observation. While the types of data are primary data and secondary data. This study uses qualitative methods using descriptive analysis. This research was conducted at the Regional Secretariat of the Ternate City Government. This research concludes that; (1). The civil servant transfer policy within the Ternate City Government is something that is normative. In matters of transfers, the policy of regional heads in carrying out mutations is recognized as something that is absolutely necessary. (2). One of the efforts to implement the Head of Service's policy is that employees who have worked for a long time receive new challenges and new assignments, as has been determined according to their duties, and the transfer of civil servants must be able to increase work productivity regarding the transfer of civil servants. (3) Transfer policy as the addition of experts to units that need it so that civil servants (PNS) improve their work performance to produce good team work in units that need it.